Swiss Permafrost Bulletin 2021 - Swiss Permafrost Monitoring Network (Swiss Permafrost Monitoring Network (PERMOS), 2022)
The Swiss Permafrost Bulletin is published annually and describes the key results of the permafrost monitoring in the Swiss Alps based on the field-data obtained in the framework of the Swiss Permafrost Monitoring Network PERMOS.
This report covers the hydrological year 2021 (1 October 2020 to 30 September 2021).
Keywords: FOS: Earth and related environmental sciences